2001
DOI: 10.1038/35075512
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for planet engulfment by the star HD82943

Abstract: Current models of the evolution of the known extrasolar planetary systems need to incorporate orbital migration and/or gravitational interactions among giant planets to explain the presence of large bodies close to their parent stars. These processes could also lead to planets being ingested by their parent stars, which would alter the relative abundances of elements heavier than helium in the stellar atmospheres. In particular, the abundance of the rare 6Li isotope, which is normally destroyed in the early ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
182
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(191 citation statements)
references
References 19 publications
5
182
1
3
Order By: Relevance
“…In particular, we will start with the families of periodic orbits corresponding to the masses of the system HD 82943. Although the elements of this system have been revised several times, the fit given by Israelian et al (2001), that we shall use here, is enough for our purpose. The elements of this fit are: m 0 = 1.05M SUN , m 1 sin i = 0.88 MJ, m 2 sin i = 1.63 MJ, a 1 = 0.73 AU, a 2 = 1.16 AU, e 1 = 0.54 ± 0.05, and e 2 = 0.41 ± 0.08.…”
Section: Factors That Affect the Stability Of A Planetary Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we will start with the families of periodic orbits corresponding to the masses of the system HD 82943. Although the elements of this system have been revised several times, the fit given by Israelian et al (2001), that we shall use here, is enough for our purpose. The elements of this fit are: m 0 = 1.05M SUN , m 1 sin i = 0.88 MJ, m 2 sin i = 1.63 MJ, a 1 = 0.73 AU, a 2 = 1.16 AU, e 1 = 0.54 ± 0.05, and e 2 = 0.41 ± 0.08.…”
Section: Factors That Affect the Stability Of A Planetary Systemmentioning
confidence: 99%
“…In many planetary systems with two planets close to each other, the two planets are in mean motion resonance. Examples are: HD 82943 (Israelian et al 2001;Mayor et al 2004), Gliese 876 (Marcy et al 2001;Rivera and Lissauer 2001), at the 2:1 resonance and 55Cnc at the 3:1 resonance . Some of these systems have large eccentricities and are evidently stable.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism would be efficient only during the first 20-30 Myr or later when the surface convection layers of the star for the first time attains its minimum size configuration (Chavero et al 2010). Israelian et al (2001Israelian et al ( , 2003 found evidence of pollution, suggesting the infall of a planet, in HD 82943 (see, however, Mandell et al 2004;Ghezzi et al 2009). The self-enrichment scenario could lead to a relative overabundance of refractories, such as Si, Mg, Ca, Ti, and the iron-group elements, compared to volatiles, such as C, N, O, S, and Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Planet migration affects the star's angular momentum, which might also have an impact on log Li . Finally, the ingestion of a planet can increase the surface lithium abundance (e.g., Montalbán & Rebolo 2002;Israelian et al 2001).…”
Section: Introductionmentioning
confidence: 99%